2004
DOI: 10.1139/w04-035
|View full text |Cite
|
Sign up to set email alerts
|

Azospirillum-plant relationships: physiological, molecular, agricultural, and environmental advances (1997-2003)

Abstract: This review presents a critical and comprehensive documentation and analysis of the developments in agricultural, environmental, molecular, and physiological studies related to Azospirillum cells, and to Azospirillum interactions with plants, based solely on information published between 1997 and 2003. It was designed as an update of previous reviews (Bashan and Levanony 1990; Bashan and Holguin 1997a), with a similar scope of interest. Apart from an update and critical analysis of the current knowledge, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
473
5
60

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 826 publications
(563 citation statements)
references
References 247 publications
25
473
5
60
Order By: Relevance
“…It is worth noting the effect of inoculation with Azospirillum spp., which according to the literature on studies conducted in Brazil, can be correlated with increased absorption of not only nitrogen, but also other nutrients, a result also reported in other countries (BASHAN; HOLGUIN, 1997;STEENHOUDT;VANDERLEYDEN, 2000;DE-BASHAN, 2004), and consistent with the results of the present study.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…It is worth noting the effect of inoculation with Azospirillum spp., which according to the literature on studies conducted in Brazil, can be correlated with increased absorption of not only nitrogen, but also other nutrients, a result also reported in other countries (BASHAN; HOLGUIN, 1997;STEENHOUDT;VANDERLEYDEN, 2000;DE-BASHAN, 2004), and consistent with the results of the present study.…”
Section: Resultssupporting
confidence: 94%
“…This result corroborates those described by Bashan, Holguin and De-Bashan (2004) that evaluated Azospirillum bacteria and the plant-Azospirillum interrelationship, and found an increase in various photosynthetic pigments (chlorophyll a and b) and photoprotective pigments (carotenoids and xanthophylls) in plants. Barassi et al (2008) reported improvements in photosynthetic parameters of the leaves, including chlorophyll content and stomatal conductance, with a higher biomass production and increased plant height of corn inoculated with Azospirillum.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The leaf area of soybean was greater in treatment with the application of A. brasilense, differing significantly from the application of Co and Mo in the seed ( Table 3). This bacterium can influence the plant growth by producing auxins, gibberellins, and cytokinins, which provide improved root growth [34] and consequently greater absorption of water and nutrients [22], resulting in more vigorous and productive plant [35,36].…”
Section: Resultsmentioning
confidence: 99%